Prevention of IL-6 signaling ameliorates toluene diisocyanate-induced steroid-resistant asthma - Shuyu Chen; Zhuoyu Chen; Yao Deng; Shanshan Zha; Li Yu; Difei Li; Zhenyu Liang; Kai Yang; Shengming Liu; Rongchang Chen (Allergology International, 2022)
Background: Accumulating evidence indicated the crucial role for interleukin 6 (IL-6) signaling in the development of allergic asthma. Yet, the role of IL-6 signaling in toluene diisocyanate (TDI)-induced mixed granulocytic airway inflammation still remains unclear. Thus, the aims of this study were to dissect the role of IL-6 signaling and to evaluate the effect of tocilizumab on TDI-induced steroid-resistant asthma. Methods: TDI-induced asthma model was prepared and asthmatic mice were respectively given IL-6 monoclonal antibody, IL-6R monoclonal antibody (tocilizumab, 5 mg/kg, i.p. after each challenge) for therapeutic purposes or isotype IgG as control. Results: TDI exposure just elevated IL-6R expression in the infiltrated inflammatory cells around the airway, but increased glycoprotein 130 expression in the whole lung, especially in bronchial epithelium. Moreover, TDI inhalation increased airway hyperresponsiveness (AHR) to methacholine, coupled with mixed granulocytic inflammation, exaggerated epithelial denudation, airway smooth muscle thickening, goblet cell metaplasia, extensive submucosal collagen deposition, dysregulated Th2/Th17 responses, as well as innate immune responses and raised serum IgE. And almost all these responses except for raised serum IgE were markedly ameliorated by the administration of IL-6 neutralizing antibody or tocilizumab, but exhibited poor response to systemic steroid treatment. Also, TDI challenge induced nucleocytoplasm translocation of HMGB1 and promoted its release in the BALF, as well as elevated lung level of STAT3 phosphorylation, which were inhibited by anti-IL-6 and anti-IL-6R treatment. Conclusions: Our data suggested that IL-6 monoclonal antibody and tocilizumab might effectively abrogate TDI-induced airway inflammation and remodeling, which could be used as a clinical potential therapy for patients with severe asthma.